Ten year follow-up study comparing conservative versus operative treatment of anterior cruciate ligament ruptures. A matched-pair analysis of high level athletes - Meuffels, D. E.; Favejee, M. M.; Vissers, M. M.; Heijboer, M. P.; Reijman, M.; Verhaar, J. (British Journal of Sports Medicine, 2009)
Objective: To compare long term outcome of highly active patients with anterior cruciate ligament ruptures treated operatively versus non-operatively. Design: We reviewed high level athletes with an anterior cruciate ligament rupture on either MRI or arthroscopic evaluation more than 10 years previously, who were treated conservatively. They were pair-matched with patients who had had an anterior cruciate ligament reconstruction with bone-patella-tendon-bone, with respect to age, gender and Tegner activity score before injury. Participants: In total 50 patients were pair-matched. Results: We found no statistical difference between the patients treated conservatively or operatively with respect to osteoarthritis or meniscal lesions of the knee, as well as activity level, objective and subjective functional outcome. The patients who were treated operatively had a significantly better stability of the knee at examination. Conclusion: We conclude that the instability repair using a bone-patella-tendon-bone anterior cruciate ligament reconstruction is a good knee stabilising operation. Both treatment options however show similar patient outcome at 10 year follow up.